2021
DOI: 10.1177/1049909121991524
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Traditional Videos With Telenovelas for Hospice Family Caregivers Education

Abstract: Background: While research has shown that hospice family caregivers (HFCG) seek additional information related to patient care, pain and symptom management, and self-care, it is unknown how the use of telenovela videos for education in hospice would be received by HFCG. Objective: To explore HFCG perceived benefits and challenges with the use of telenovelas as compared to traditional educational videos during online support group. Methods: A mixed methods study with a concurrent triangulated design that analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another study testing an educational booklet found modest improvements in EoL knowledge but noted improvement in outcomes varied based on the caregiver's stage of caregiving. Finally, a study using telenovela videos for hospice family caregivers found that caregivers reported better content recall and triggered more conversations about patient care 25 . The videos in this study are meant to be seen as an additional resource to complement the existing support provided by hospice care.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another study testing an educational booklet found modest improvements in EoL knowledge but noted improvement in outcomes varied based on the caregiver's stage of caregiving. Finally, a study using telenovela videos for hospice family caregivers found that caregivers reported better content recall and triggered more conversations about patient care 25 . The videos in this study are meant to be seen as an additional resource to complement the existing support provided by hospice care.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, a study using telenovela videos for hospice family caregivers found that caregivers reported better content recall and triggered more conversations about patient care. 25 The videos in this study are meant to be seen as an additional resource to complement the existing support provided by hospice care. Future studies are needed to test the efficacy of these videos with a larger sample of caregivers.…”
Section: Discussionmentioning
confidence: 99%